Effects of a monocarboxylate transport 1 inhibitor, AZD3965, on retinal and visual function in the rat. (13th September 2020) - Allen, Annette E.; Martin, Elizabeth A.; Greenwood, Katherine; Grant, Claire; Vince, Peter; Lucas, Robert J.; Redfern, William S.
Abstract : Background and Purpose: Inhibition of monocarboxylate transport 1 (MCT1) is of interest in targeting highly glycolytic tumours. However, MCT1 is expressed in retina, and so inhibition of MCT1 could affect retinal function. Experimental Approach: AZD3965, an MCT1 inhibitor selected for clinical development, and two additional MCT1 inhibitors were evaluated for effects on visual acuity in albino (Han Wistar) rats. The effects of AZD3965 on visual acuity and electroretinography (ERG) were further investigated in pigmented (Long‐Evans) rats, with dosing for up to 7 days. Key Results: All three MCT1 inhibitors reduced visual acuity within 2 h of dosing, suggesting a class effect. The deficit caused by AZD3965 (1, 000 mg·kg −1 p.o. per day for 4 days) in Long Evans rats recovered to pre‐dose levels 7 days after cessation of dosing. AZD3965 (50 to 1, 000 mg·kg −1 p.o.) reduced the amplitude of scotopic a‐ and b‐waves, and photopic b‐wave of the ERG in a dose‐related fashion, within 2 h of dosing. The effects on the scotopic ERG had diminished by Day 7 of dosing, demonstrating partial restoration of function despite continued treatment. Seven days after cessation of dosing at the highest dose tested (1, 000 mg·kg −1 ), there was recovery of both scotopic a‐ and b‐ waves and, to a lesser extent, photopic b‐wave. ERG was affected at lower plasma exposures than was visual function. Conclusions and Implications: This study clarifies the role of the MCT1 transporter in retinal function. The monitorability of the functional effects on the retina enabled safe clinical use of AZD3965.